-8v+3v=-8(-3-3v)-4(3v+6)

Simple and best practice solution for -8v+3v=-8(-3-3v)-4(3v+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8v+3v=-8(-3-3v)-4(3v+6) equation:



-8v+3v=-8(-3-3v)-4(3v+6)
We move all terms to the left:
-8v+3v-(-8(-3-3v)-4(3v+6))=0
We add all the numbers together, and all the variables
-8v+3v-(-8(-3v-3)-4(3v+6))=0
We add all the numbers together, and all the variables
-5v-(-8(-3v-3)-4(3v+6))=0
We calculate terms in parentheses: -(-8(-3v-3)-4(3v+6)), so:
-8(-3v-3)-4(3v+6)
We multiply parentheses
24v-12v+24-24
We add all the numbers together, and all the variables
12v
Back to the equation:
-(12v)
We add all the numbers together, and all the variables
-17v=0
v=0/-17
v=0

See similar equations:

| -5a+2=7a-46 | | 32=2x+8x | | -7c-3=-83+3c | | X+3x-150=3,150 | | 19s-9s+2=12 | | -7(7-8z)=15-344 | | 1.2/3x=6 | | 51+4a=9a+6 | | 45=-10x-5x | | 12/3x=6 | | 64=-5x+13x | | 4+3+x=11 | | 8-(2n-2)=6-3n | | 3x+5=3.25x | | 11x+6=7x+102 | | 5p+3/4=3p+7/8 | | 7-(2z-6)=9-3z | | 4+3(3)=9x | | 27=7x-4x | | 6q-16q+17q+-4q=-12 | | 3x+1=4x+2/3 | | 5k=17-2 | | 1x/55=180 | | a(a-1)(a+3)=0 | | 5+2x=10x-2x | | 4b=-9+3 | | 2(x+8)-2=35-5x | | 5+4(3x-3)=-2(3x-4)+8x | | (0.5x^2)-(4.5x)+3.5=0 | | 2x+17=(x+5)(x+1) | | 17=3m+2 | | -8(z+2)=+3z |

Equations solver categories